Fabrication and characterization of the normally,off N-channel lateral 4H-SiC metal-oxide-semiconductor field-effect transistors - 宋庆文 汤晓燕 何艳静 唐冠男 王悦湖 张艺蒙 郭辉 贾仁需 吕红亮 张义门 张玉明 (Chinese physics B, 2016)
In this paper, the normally-off N-channel lateral 4H-SiC metal-oxide-semiconductor field-effect transistors （MOSF- FETs） have been fabricated and characterized. A sandwich- （nitridation-oxidation-nitridation） type process was used to grow the gate dielectric film to obtain high channel mobility. The interface properties of 4H-SiC/SiO2 were examined by the measurement of HF l-V, G-V, and C-V over a range of frequencies. The ideal C-V curve with little hysteresis and the frequency dispersion were observed. As a result, the interface state density near the conduction band edge of 4H-SiC was reduced to 2 x 1011 eV-l.cm-2, the breakdown field of the grown oxides was about 9.8 MV/cm, the median peak field- effect mobility is about 32.5 cm2.V-1 .s-1, and the maximum peak field-effect mobility of 38 cm2-V-1 .s-1 was achieved in fabricated lateral 4H-SiC MOSFFETs.